2008
DOI: 10.1016/j.jembe.2007.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Growth rate and age effects on Mya arenaria shell chemistry: Implications for biogeochemical studies

Abstract: The chemical composition of bivalve shells can reflect that of their environment, making them useful indicators of climate, pollution, and ecosystem changes. However, biological factors can also influence chemical properties of biogenic carbonate. Understanding how these factors affect chemical incorporation is essential for studies that use elemental chemistry of carbonates as indicators of environmental parameters. This study examined the effects of bivalve shell growth rate and age on the incorporation of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 49 publications
3
40
1
Order By: Relevance
“…Average shell lengths (± SE) from 15, 20, and 24°C treatments were 2.57 ± 0.13 mm, 3.10 ± 0.11 mm, and 5.05 ± 0.21 mm, respectively. Shell E:Ca did not vary significantly over this size range (Strasser et al 2008); we therefore assumed that shell size differences did not affect our results.…”
Section: Rearing Conditionsmentioning
confidence: 78%
See 1 more Smart Citation
“…Average shell lengths (± SE) from 15, 20, and 24°C treatments were 2.57 ± 0.13 mm, 3.10 ± 0.11 mm, and 5.05 ± 0.21 mm, respectively. Shell E:Ca did not vary significantly over this size range (Strasser et al 2008); we therefore assumed that shell size differences did not affect our results.…”
Section: Rearing Conditionsmentioning
confidence: 78%
“…Gillikin et al (2005), however, carefully documented the relationship between environmental factors and Sr uptake in 2 species of marine bivalves with aragonitic shells and concluded that Sr:Ca ratios in shell are regulated by biological processes rather than thermodynamics. Studies of growth rate effects on Sr incorporation into Mya arenaria juvenile shell have produced both positive and negative correlations to growth rate for juvenile shells reared in the same conditions (Strasser et al 2008). These ambiguous results lend support to the idea that Sr incorporation may involve a number of physical and biological processes.…”
Section: Strontium Uptakementioning
confidence: 97%
“…Only Na:Ca was increased 2-fold on the sulcal axis, while Sr:Ca was similar between both axes. These patterns may have arisen simply due to differences in precipitation rates and therefore incorporation dynamics of elemental impurities (Strasser et al 2008, Walther et al 2010). In addition, other studies have quantified the elemental composition of the endolymph fluid from which the otolith is mineralized and found heterogeneity between dissolved elements and proteins in the proximal and distal regions of the endolymph (Payan et al 1999(Payan et al , 2004b.…”
Section: Chemistry Differences In Otolith Growth Axismentioning
confidence: 99%
“…A careful comparison of the results obtained from shell cleaned using the pre-ablation technique used here and other chemical cleaning techniques involving the use of hydrogen peroxide (e.g. Strasser et al 2008) should also be undertaken to determine the effect of cleaning methodology. Furthermore, multiple sampling events should be incorporated to understand how elemental fingerprints change over seasonal or annual scales.…”
Section: Discussionmentioning
confidence: 99%
“…Using stainless steel forceps, valves were split open, the flesh was removed and the shells were physically cleaned to remove any large adhering particles. Valves were placed into 50 ml centrifuge tubes filled with deionised water (which was maintained at a resistivity of <1 MΩ cm) and sonicated for 2 min to remove any remaining organic matter (Strasser et al 2008). The water was drained, and the shells were allowed to air dry.…”
Section: Sample Preparationmentioning
confidence: 99%